Temporal variation in oral microbiome composition of patients undergoing autologous hematopoietic cell transplantation with keratinocyte growth factor - Bohn, Bruno; Chalupova, Miroslava; Staley, Christopher; Holtan, Shernan; Maakaron, Joseph; Bachanova, Veronika; El Jurdi, Najla (BMC microbiology, 2023)
INTRODUCTION: Autologous hematopoietic cell transplantation (AHCT) is a well-established treatment for lymphoma. Unintended effects of this therapy include oral mucositis (OM) and gastrointestinal toxicities, resulting in poor clinical outcomes. The gut microbiome has been previously linked to transplant toxicities among allogeneic recipients, but little is known about the effects of AHCT on the oral microbiome. METHODS: Seven patients with non-Hodgkin or Hodgkin lymphoma undergoing AHCT with palifermin (keratinocyte growth factor) were included. Buccal swab samples were collected at baseline and 14- and 28-days post-treatment. Oral microbial communities were characterized with 16 S rRNA amplicon sequencing. Temporal trends in community composition, alpha diversity, and beta diversity were investigated. RESULTS: A significant reduction in the relative abundance of the genera Gemella and Actinomyces were observed from baseline. No significant temporal differences in alpha diversity were observed. Significant changes in beta diversity were recorded. CONCLUSION: Results of this pilot study suggest treatment with AHCT and palifermin affects the oral microbiome, resulting in temporal shifts in oral microbial community composition. Future studies are warranted to confirm these trends and further investigate the effects of AHCT on the oral microbiome and how these shifts may affect health outcomes.
Keywords: Hematopoietic cell transplantation; Autologous; Oral microbiome; mikrobiota; lidé; Hematopoietic Stem Cell Transplantation; transplantace hematopoetických kmenových buněk; Pilot Projects; Microbiota; Fibroblast Growth Factor 7; střevní mikroflóra; pilotní projekty; fibroblastový růstový faktor 7; Gastrointestinal Microbiome; Humans